The Diaspora, Governance and Development in Ekiti South-Western Nigeria. - Oke, Leke; Adu, F. M. (Advances in Social Sciences Research Journal, 2018)
Scholars lay emphasis on development as consequent upon actions of government and civil societies. This implies that the diaspora as a civil society can impact institutional and infrastructural reforms to achieve physical indices of development. Good governance can create the positive environment for the diaspora to positively impact governance. Both can work in tandem to create positive growth in the society. Ekiti state, a subunit of the 36 states of the Nigerian Federation is underdeveloped and largely a civil service and an agrarian state thus requiring government’s partnership with the diaspora and other public spirited entities for its development and sustenance. This paper examines the symbiotic relationship between the Diaspora and government in piloting the affairs of the state. It is within the purview of the paper that the onerous task of state building and development is complementary involving government and interest groups among which are the Diaspora. The paper canvasses all-inclusive governance for the development of the agrarian and civil service state.